Advances in mobile and wireless communications : views of the 16th IST Mobile and Wireless Communication Summit - IST Mobile & Wireless Communications Summit (16th : 2007 : Budapest, Hungary); Bito, Janos; Bakki, Pťer; Frigyes, Istvan (Berlin : Springer, 2008)
Includes bibliographical references and index